Spectroscopy for identification of plasma sources for lithography and water window imaging. (August 2015) - O'Sullivan, Gerry; Dunne, Padraig; Higashiguchi, Takeshi; Li, Bowen; Lokasani, Ragava; Long, Elaine; Ohashi, Hayato; O'Reilly, Fergal; Sheridan, Paul; Sheil, John; Sokell, Emma; Suzuki, Chihiro; et al.
Synopsis: We report on the result of an extensive study of the extreme ultraviolet (EUV) and soft x-ray spectra from laser produced plasmas of a number of medium and high Z metals undertaken to identify potential sources for use with multilayer mirrors as sources for lithography and water window imaging and cell tomography.